Chitosan-reinforced cellulosic bionogels: Viscoelastic and antibacterial properties. (1st February 2020) - Villar-Chavero, M. Mar; Domínguez, Juan C.; Alonso, M. Virginia; Oliet, Mercedes; Rodriguez, Francisco
Highlights: Cellulosic bionogels reinforced with chitosan (0.25−1 wt/wt.%) were developed. Increasing chitosan loading improved the viscoelastic properties of the bionogels. The bionogel with 1 wt/wt.% chitosan had the greatest viscoelastic properties. Chitosan-reinforced cellulosic bionogels presented antibacterial properties. Abstract: New chitosan-reinforced cellulosic bionogels were successfully formulated with different chitosan loadings (0.25, 0.5, 0.75, and 1 wt/wt. %). These materials were developed using cholinium lysinate, a bio-ionic liquid, being an ecological alternative to conventional ionogels. The rheological properties of these materials showed that all the studied viscoelastic properties were higher (elastic moduli, G'; loss moduli, G"; and complex viscosity, η*) as the chitosan loading increased. The reinforced bionogels were physical weak gels, and the proposed mechanism of formation was by hydrogen bonds. The bionogel with 1 wt/wt. % chitosan loading exhibited the highest viscoelastic properties (for 4 Hz, G': 552 kPa, G": 99 kPa, and η*: 22 kPa·s). Regarding the antibacterial properties, these gels showed a good inhibitory capacity to S. aureus and E. coli, especially against the latter bacterium. For these reasons, these novel ecofriendly gels are promising in the pharmaceutical/medical and biosensors sectors to develop new functional materials.